Fostering biotechnology on the productivity and development of agricultural SMEs (Zimbabwe) - Ngoni Munyawarara (Goodwood Publishing, 2020)
Purpose: This study scrutinizes the application of biotechnology in fostering the productivity of agricultural SMEs in Zimbabwe over the period 2019-2020. Fostering biotechnology around the world is significantly attracting much attention from agricultural entrepreneurs who have been lacking business productivity initiatives. As much this study attempts to unravel whether biotechnology is the spring bed for stimulating the productivity of agricultural SMEs to attain food security and nutriment. Research Methodology: A survey was used to get biotechnology data from archives of the National Biotechnology Association of Zimbabwe, concerning the use of biotechnology research in seeking to improve productivity by agricultural SMEs. Results: The study showed that fostering biotechnology has demonstrable benefits that help SMEs to grow and increase food nutriment. The study recommended that investing in biotechnology has returns which are most apparent for SMEs to increase productivity and competitiveness in Zimbabwe Limitation: The lack of a single study is a complex nature in the study and seemingly different instruments could produce a detailed analysis. Contribution: The study encourages fostering biotechnology to improve the productivity and development of agricultural SMEs in Zimbabwe to attain food security and nutriment and poverty reduction. Keywords: Biotechnology, Agriculture, SMEs, Development, Productivity, Food security